INFORMATION TECHNOLOGY AS A CATALYST OF INNOVATIVE CHANGES IN ENTERPRISES - Gródek-Szostak, Zofia; Kajrunajtys, Danuta; Ochoa Siguencia, Luis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The subject of this research study is the applications of Information Technology (IT) to support management. This is not the sole use of IT methods and means in enterprises, however, the issues related to the automation of technological processes and software for these purposes are not the subject of these considerations. The aim of this research study is to show the innovative role of IT as a factor that enables meeting the challenges posed by managers, such as improving work efficiency, accelerating (reducing time of) handling orders, entering into competition on previously inaccessible markets, and generating the value added, which goes far beyond the capabilities of a single business entity. The business model includes collaboration unhindered by the territorial distribution of individuals, or time zone differences. The measure of effectiveness is the achieved result, and the recipient of the value thus created is not interested in where and how this value is created. Dynamically changing market expectations and the needs of recipients force the reconfiguration of the manufacturing system, which is a feature of virtual workplaces.